Sexual History Taking: An Opportunity to Reduce Health Disparities. (20th May 2022) - Mintz, Laura Janine; Moore, Scott Emory
Abstract: Sexual history taking is an important part of caring for any clinical population. However, the topic is often wrapped in discomfort that makes it more challenging than it needs to be for both the provider and the individual providing the history. The act of taking an effective sexual history is more than simply asking all the right questions in the right ways; it requires an awareness of the impact of the clinical environment, the provider's own comfort with the content, and an awareness of any personal biases. In this study, we provide a framework for evaluating and addressing many of these factors as well as providing key points for consideration as a health care provider of any level. We offer several concrete strategies for including these strategies and processes in multiple clinical environments.